The Theory of Neural Cognition Applied to Robotics. (23rd June 2015) - Touzet, Claude F.
The Theory of neural Cognition (TnC) states that the brain does not process information, it only represents information (i.e., it is 'only' a memory). The TnC explains how a memory can become an actor pursuing various goals, and proposes explanations concerning the implementation of a large variety of cognitive abilities, such as attention, memory, language, planning, intelligence, emotions, motivation, pleasure, consciousness and personality. The explanatory power of this new framework extends further though, to tackle special psychological states such as hypnosis, the placebo effect and sleep, and brain diseases such as autism, Alzheimer's disease and schizophrenia. The most interesting findings concern robotics: because the TnC considers the cortical column to be the key cognitive unit (instead of the neuron), it reduces the requirements for a brain implementation to only 160, 000 units (instead of 86 billion). A robot exhibiting human-like cognitive abilities is therefore within our reach.